Evaluation of the Visibility and the Course of the Lingual Foramen Using Orthopantomogram - Yuvaraj, Ashna; Sekar, Durairaj; Lakshmanan, Ganesh (Journal of Neonatal Surgery, 2025)
Introduction: Lingual foramen are usually located in the midline, level with or superior to the genial tubercles. The success of implant placements is dependent on the radiological examination, which helps the clinician to determine the parameters of implant placement by revealing the structures like the course of the nerves, location of foramina, height, and shape of alveolar bone, etc. (1). Aim: The present study was done to evaluate the visibility and course of the lingual foramen using an orthopantomogram. Materials and methods: The study consisted of 2000 OPG's ranging from 18 years to 75 years at Saveetha Dental College & Dental Hospital, Chennai to evaluate the appearance and visibility of the lingual foramen in the mandible on Orthopantomogram. OPG's with malformations, trauma, musculoskeletal disorders were excluded from the study. Results: Out of 2000 OPG's the visibility of lingual foramen in males was 74% when compared to females which were 68% (Figure 2). The visualization of the presence of lingual foramen between all the age groups ranging from 18-75 was almost the same (Figure 3). Conclusion: OPG can be considered for the cognizance of the position of anatomical structures during the major maxillofacial surgeries and placement of endosseous implants to provide suﬃcient information.